The Influence of COVID-19 Severity on Maternal and Perinatal Outcomes: Evidence from a Cohort Study in Indonesia - Aziz, Muhammad Alamsyah; Nurdiawan, Windi; Avivi, Safiya Fathina; Wahyudi, Kurnia; Irianti, Setyorini; Fauzi, Ali Amali; Lillah, Alfarisi Syukron; Mariana, Ana; Nugrahani, Annisa Dewi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aimed to assess the association between COVID-19 severity and maternal and neonatal outcomes at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.Methods: A retrospective cohort study was conducted among pregnant women with confirmed COVID-19 who delivered between March 1, 2020, and March 31, 2022. Patients were categorized by disease severity (asymptomatic, mild, moderate, severe, or critical). Demographic, clinical, maternal, and neonatal data were collected. Statistical analyses included Fisher’s exact and Kruskal-Wallis tests for bivariate analysis and Poisson regression for multivariate analysis (significance level α = 0.05).Results: Among 199 pregnant women, most were asymptomatic (42.7%) or had mild symptoms (37.2%). Higher COVID-19 severity was significantly associated with increased ICU/semi-ICU admission and oxygen therapy, as well as neonatal complications. After adjustment, moderate to critical cases showed significantly increased risks for ICU/semi-ICU care (p = 0.012, aRR 14.6; 95% CI: 1.8–118.2) and oxygen therapy (p = 0.001, aRR 12.2; 95% CI: 2.7–55.3). Mild cases were not linked to adverse outcomes.Conclusion: Moderate to critical COVID-19 during pregnancy is associated with higher risks of adverse maternal and neonatal outcomes, emphasizing the importance of early detection and close monitoring.Dampak Keparahan COVID- 19 pada Luaran Kehamilan: Studi Kohort di IndonesiaAbstrakTujuan: Penelitian ini bertujuan mengevaluasi hubungan antara tingkat keparahan COVID-19 dan luaran kehamilan serta neonatal di RSUP Dr. Hasan Sadikin, Bandung.Metode: Metode yang digunakan pada penelitian ini adalah kohort retrospektif pada ibu hamil dengan konfirmasi COVID-19 yang melahirkan antara 1 Maret 2020 hingga 31 Maret 2022. Pasien dikelompokkan berdasarkan tingkat keparahan (asimtomatik, ringan, sedang, berat, kritis). Data demografi, klinis, serta luaran ibu dan bayi dikumpulkan. Analisis statistik dilakukan menggunakan SPSS, dengan uji Fisher’s exact dan Kruskal-Wallis untuk bivariat, serta regresi Poisson untuk multivariat (α=5%).Hasil: Hasil penelitian menunjukkan dari 199 ibu hamil yang dianalisis, mayoritas bersifat asimtomatik (42,7%) atau ringan (37,2%). Keparahan penyakit yang lebih tinggi secara signifikan berhubungan dengan peningkatan kebutuhan perawatan ICU/semi-ICU dan terapi oksigen, serta komplikasi neonatal. Setelah penyesuaian, COVID-19 sedang–kritis berkorelasi dengan peningkatan risiko ICU/semi-ICU (p=0,012, aRR 14,6; 95% CI 1,8–118,2) dan terapi oksigen (p=0,001, aRR 12,2; 95% CI 2,7–55,3). Kasus ringan tidak menunjukkan hubungan dengan luaran buruk.Kesimpulan: Keparahan COVID-19 sedang hingga kritis pada kehamilan meningkatkan risiko luaran buruk sehingga diperlukan identifikasi dini dan pemantauan ketat.